DIGITAL MARKETING EFFORTS IN INCREASING SALES RESULTS OF PRISONERS' WORK ACTIVITIES AT CIPINANG CLASS 1 PRISON - Ronaldo Christian; Denny Nazaria Rifani (Polteknik Ilmu Pemasyarakatan, 2021)
This study discusses Digital Marketing's efforts in increasing the sales results of inmates' work activities at the Cipinang Class I Correctional Institution, in the implementation of independence activities at the Penitentiary which focuses on work activities, of course, training and good and correct strategies are needed in marketing the results of work activities. The purpose of this study is to find out how to increase the sales results of inmates' work activities through Digital Marketing efforts and the obstacles faced in carrying out the process of increasing the sales results of inmates' work activities at the Cipinang Class I Correctional Institution. The type of research used in this study is a qualitative approach. Based on this research, it is known that the marketing of the sales of work activities at the Cipinang Class I Correctional Institution uses conventional methods and online marketing methods. However, the implementation has not run optimally, because only online partnerships are carried out by Cipinang Class 1 Correctional Instituion in marketing their products to the public online. Keywords : Digital Marketing, Work Activities, Prisoners